PENGARUH PERSEPSI DAN CARA BELAJAR TERHADAP HASIL BELAJAR SENI RUPA SISWA SMA PGRI 2 PADANG - INTAN TANITA DEVI, Dra. Zubaidah, M.Pd., Drs. Erwin A, M.Sn. (Universitas Negeri Padang, 2016)
Problems that take place during the learning process which refers to the influence of perception and learning the art student learning outcomes. Purpose of this study was to describe the influence of perception and learning of the results. This research is a quantitative research associative with a sample of 67 students by using a sample purposive sampling technique. Data consists of primary data in the from of a questionnaire completed student, and data secondary to the learning outcome. (1) the research findings that influence perception of the learning outcomes of -1,36%. (2) the way of learning to the learning outcomes of -0,93. (3) perception and learning to the learnimg outcomes at 2,8% which is very low.Key word: influence perception, learning and learning outcomes